Concordance of Dermoscopic Findings and Wood’s Lamp Findings in Melasma Patients - Nasar, Amna; Aamir Habib; Qamar Ud Din; Summaya Saleem; Sadaf Jamshaid; Usman Sajid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find the concordance of Dermoscopic and Wood’s lamp findings in melasma patients.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital, Kharian Pakistan, from Nov 2020 to Sep 2021.Methodology: A total of sixty patients clinically classified as melasma were enrolled in the study. Clinical assessment was done, and patients were examined with Wood’s lamp and Dermoscope, and findings were recorded.Results: The results of concordance of Wood’s lamp findings and Dermoscopic findings were significant as analysed by Kappa Statistics where value of k was 0.597 and p-value was